Climate Smart Agriculture (CSA) Technology Portfolios for Rice-Based Systems (Saline, Upland, and Lowland Ecosystems) - Gonsalves, Julian Francis; Or, Thy; Yim, Soksophors; Tong, Chantheang (2018)
This Primer for Cambodia is describing ways to improve rice productivity by improving the management of soils and crops such as: further diversification of varieties, the inclusion of stress-tolerant rice varieties, the introduction of the System of Rice Intensification (SRI), re-introduction of legumes, and management of crop residues and fertilizers.